Sociodrama in the Training of Social Educators: An Exploratory Research - Veiga, Sofia (2016)
The object of this study is Sociodrama as a training method within two subjects in the Social Education degree. Using a qualitative investigation, the intention was to understand how this method contributed, over two academic years, to promote the personal, social and professional development of students. In the four groups that were studied it was shown that the Sociodrama method enables openness to multiple perspectives upon reality, the sharing of feelings, and the creative search of solutions to solve problems and difficulties, creating conditions towards the development of flexibility and spontaneity essential in the professional practice.